The Microvascular Peroneal Artery Perforator Flap as a "Lifeboat" for Pedicled Flaps - Jakubietz, Rafael G.; Jakubietz, Danni F.; Horch, Raymund E.; Gruenert, Joerg G.; Meffert, Rainer H.; Jakubietz, Michael G. (Plastic and Reconstructive Surgery Global Open, 2019)
Background: Pedicled perforator flaps have expanded reconstructive options in extremity reconstruction. Despite preoperative mapping, intraoperative findings may require microvascular tissue transfer when no adequate perforators can be found. The free peroneal artery perforator flap may serve as a reliable back-up plan in small defects. Methods: In 16 patients with small soft tissue defects on the upper and lower extremities, perforator-based propeller flaps were planned. The handheld Doppler device was used to localize potential perforators for a propeller flap in close proximity to the defect. Perforators of the proximal peroneal artery were also marked to allow conversion to microvascular tissue transfer. Results: In 6 cases, no adequate perforators were found intraoperatively. In 4 patients, the peroneal artery perforator flap was harvested and transferred. The pedicle length did not exceed 4 cm. No flap loss occurred. Conclusions: When no adequate perforator capable of nourishing a propeller flap can be found intraoperatively, the free peroneal artery flap is a good option to reconstruct small soft tissue defects in the distal extremities. The short vascular pedicle is less ideal in cases with a large zone of injury requiring a more distant site of anastomosis or when recipient vessels are located in deeper tissue planes.
CRIS-Team WoS Importer:2019-11-22